2023
DOI: 10.1111/jocn.16947
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nurse‐led self‐care interventions on health outcomes among people with heart failure: A systematic review and meta‐analysis

Zehao Huang,
Ting Liu,
Ruitong Gao
et al.

Abstract: AimTo estimate the effects of nurse‐led self‐care interventions on people with heart failure (HF).BackgroundResearch evidence of the effects of nurse‐led HF self‐care interventions on patient outcomes is scant.DesignA systematic review and meta‐analysis of randomised controlled trials (RCTs).Data SourcesSix databases (MEDLINE, Embase, Web of Science, CENTRAL, CINAHL and PsycINFO) were searched from the inception to December 2022 to identify eligible studies.MethodsRCTs published in English that evaluated the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…However, we would like to point out some concerns regarding the high heterogeneity of QOL outcomes that warrant further discussion. The authors (Huang et al, 2024) found a large effect size for improvement in QOL with nurse-led interventions (standardised mean difference: 0.83), but noted considerable heterogeneity (I 2 = 84%).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…However, we would like to point out some concerns regarding the high heterogeneity of QOL outcomes that warrant further discussion. The authors (Huang et al, 2024) found a large effect size for improvement in QOL with nurse-led interventions (standardised mean difference: 0.83), but noted considerable heterogeneity (I 2 = 84%).…”
mentioning
confidence: 97%
“…Accordingly, we conducted a prediction interval analysis using the data reported in the original meta-analysis (Huang et al, 2024).…”
mentioning
confidence: 99%
See 1 more Smart Citation